Update on Hypermetabolism in Pediatric Burn Patients - Layon, Sarah A.; Williams, Austin D.; Parham, Matthew J.; Lee, Jong O. (Seminars in Plastic Surgery, 2024)
Despite advancements in pediatric burn care, the profound hypermetabolic response associated with severe burns remains a multifaceted challenge throughout the continuum of care. Understanding the various physiologic disturbances that constitute hypermetabolism is crucial for a thorough evaluation and for implementing appropriate surgical and nonsurgical interventions. In this article, we describe the pathophysiology and treatment of hypermetabolism in pediatric burn patients with a focus on reducing resting energy requirements, minimizing infection, and optimizing nutrition for patients undergoing frequent surgical intervention.
Keywords: burn injury; pediatric; hypermetabolism; catabolism; stress; inflammation